EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATERI ARITMATIKA SOSIAL DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SEKABUPATEN PACITAN - Anggraheni, Retno; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of research were to find out: (1) which learning model provided better student learning achievement, Problem based Learning (PBL) or Numbered Heads Together (NHT) type of Cooperative Learning or direct learning model, (2) which students had better mathematics learning achievement, those with auditory, or visual, or kinesthetic learning style,  (3) in each learning model, which one had mathematics learning achievement better, whether the students with auditory, those with visual or those with kinesthetic learning style, (4)  in each learning style, which one provided better mathematics learning achievement, Problem based Learning (PBL) or Numbered Heads Together (NHT) type of Cooperative Learning or direct learning model. This study was a quasi experimental research with a 3 x 3 factorial design. The population of research was all of the VII graders of Junior High Schools in Pacitan Regency. The sample was taken using stratified cluster random sampling. The sample of research consisted of 242 students: 82 students for the experiment 1, 80 students for experiment 2 and 80 students for control classes. Considering the result of hypothesis testing, the following conclusions could be drawn. (1) The Problem Based Learning, the NHT type of cooperative learning, and direct learning models provided equal mathematics learning achievement. (2) The students with visual learning style had the mathematics learning achievement equal to those with kinesthetic one. Those with visual learning style had the mathematics learning achievement better than those with auditory one. Those with kinesthetic learning style had the mathematics learning achievement better than those with auditory one. (3) In PBL learning model, the students with visual learning style had the mathematics learning achievement better than those with auditory one, but those with visual learning style had the mathematics learning achievement equal to those with kinesthetic one, and those with auditory learning style had the mathematics learning achievement equal to those with kinesthetic one. In NHT type of cooperative learning model, the students with visual learning style had the mathematics learning achievement equal to those with auditory one and those with visual learning style had the mathematics learning achievement equal to those with kinesthetic one, but those with auditory learning style had the mathematics learning achievement better than those with kinesthetic one. In direct learning model, the results of the three learning style provided equal learning achievement. (4) In the students with visual learning style, PBL model provided learning achievement equal to the NHT type of cooperative learning one, PBL did better than the direct one, and the NHT type did better than the direct one. In auditory learning style, PBL model provided the learning achievement equal to the NHT type, while PBL did better than the direct one, and the NHT type did better than the direct one. In those with kinesthetic learning style, PBL model provided learning achievement equal to the NHT type of cooperative learning one, PBL did better than the direct one, and the NHT type did better than the direct one. In auditory learning style, PBL model provided the learning achievement equal to the NHT type, PBL provided learning achievement equal to the direct one, and the NHT type did better than the direct one. Keywords: Problem Based Learning (PBL), Numbered Heads Together (NHT), student learning style.